2022
DOI: 10.33647/2074-5982-18-3-128-132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ornithine Aspartate and Empagliflozin on Memory Deficit Symptoms in Experimental Steatohepatitis

Abstract: In this study, L-ornithine L-aspartate and empagliflozin were evaluated in terms of their potential effects on the hippocampus-dependent memory status in non-alcoholic steatohepatitis (NASH) in C57Bl/6 mice. NASH was found to be associated with an early transient decrease in the short-term recognition memory as well as a progressive reduction in the short-term spatial memory. L-ornithine L aspartate effectively prevented the impairment of recognition, rather than spatial, memory. At the same time, empagliflozi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…In our study, we observed a long-term decrease in spatial memory, as shown in the SATM test, but no change in object-recognition memory. Consistent with our previous results [69], this discrepancy could possibly be explained by the stronger dependency of spatial memory rather than recognition memory on functional hippocampal tissue volume [70].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we observed a long-term decrease in spatial memory, as shown in the SATM test, but no change in object-recognition memory. Consistent with our previous results [69], this discrepancy could possibly be explained by the stronger dependency of spatial memory rather than recognition memory on functional hippocampal tissue volume [70].…”
Section: Discussionsupporting
confidence: 89%